2020
DOI: 10.1016/j.jaad.2020.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Surgical margins required for basal cell carcinomas treated with Mohs micrographic surgery according to tumor features

Abstract: 1. Trump DJ. Proclamation on declaring a national emergency concerning the novel coronavirus disease (COVID-19) outbreak. Available at: https://www.whitehouse.gov/presidential-actions/ proclamation-declaring-national-emergency-concerning-novelcoronavirus-disease-covid-19-outbreak/. 2020. Accessed October 12, 2020. 2. CARES Act, S.3548, 116th Congress. Available at: https://www. congress.gov/bill/116th-congress/senate-bill/3548/text. 2020. Accessed October 11, 2020. 3. Gisondi P, Piaserico S, Conti A. Dermatolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Regarding high-risk location, there is a statistically significant difference in a number of stages between tumors located in the periocular region and tumors of the ear, nose, or perioral area, with periocular BCCs requiring more stages of surgery. Although location on high-risk areas was shown to be associated with a higher number of stages in previous studies, 4 , 5 , 7 the specification and comparison between various high-risk areas are more rarely mentioned in the literature.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Regarding high-risk location, there is a statistically significant difference in a number of stages between tumors located in the periocular region and tumors of the ear, nose, or perioral area, with periocular BCCs requiring more stages of surgery. Although location on high-risk areas was shown to be associated with a higher number of stages in previous studies, 4 , 5 , 7 the specification and comparison between various high-risk areas are more rarely mentioned in the literature.…”
Section: Discussionmentioning
confidence: 95%
“…This was not according to other studies, in which preoperative size was a significant predictor of larger margins and number of stages, especially when tumors had > 20 mm. 7 , 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 91 , 92 A recent study that evaluated margins (in mm) required for primary BCC clearance showed that the most significant factors related to larger margins were superficial, micronodular, infiltrative, and morpheaform subtypes; whereas clinically well-defined tumors were associated with smaller margins. 93 …”
Section: Basal Cell Carcinomamentioning
confidence: 99%